2015
DOI: 10.1063/1.4913982
|View full text |Cite
|
Sign up to set email alerts
|

Common features of particle beams and x-rays generated in a low energy dense plasma focus device

Abstract: Features of energetic charged particle beams and x-ray emission in a low energy (1-2 kJ) plasma focus (DPF) device are described and the possible mechanism are explained based on circuit analyses and energy balance in the DPF system. In particular, the resistance and the voltage across the plasma column are estimated to explain the mechanisms of the generation of particle beams and hard x-ray. The analysis shows that the total inductance of a DPF might have played a role for enhancement of the particle beams a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In this letter a new dense plasma focus configuration with an additional cylindrical floating electrode (DPF-FE) between the conventional anode and cathode in a Mather-type plasma focus device will be introduced. The measured tube voltages and discharge current have been interpreted by using circuit analyses technique [5][6][7][8][9][10] and the occurrence of breakdown phase, axial phase, and compression phase has been discussed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this letter a new dense plasma focus configuration with an additional cylindrical floating electrode (DPF-FE) between the conventional anode and cathode in a Mather-type plasma focus device will be introduced. The measured tube voltages and discharge current have been interpreted by using circuit analyses technique [5][6][7][8][9][10] and the occurrence of breakdown phase, axial phase, and compression phase has been discussed.…”
mentioning
confidence: 99%
“…I is the discharge current that is measured by Rogowski coil and L ext = 70 nH [5][6][7][8][9][10]. Based on eq.…”
mentioning
confidence: 99%
“…The previously reported results showed multiple radiation peaks of ion beams [9,10] and X-ray signals [11], presumably caused by anomalous resistance during the final stage of plasma focus. The common features of the charged-particle beam and X-ray emission have been analysed quantitatively based on the voltage across the plasma column during the pinch phase [12]. The analyses have shown that plasma resistance may reach 0.2 Ω during the phase with anomalous resistances and the minimum anode voltage to generate hard X-rays in this phase is about 13 kV [12].…”
mentioning
confidence: 99%
“…The common features of the charged-particle beam and X-ray emission have been analysed quantitatively based on the voltage across the plasma column during the pinch phase [12]. The analyses have shown that plasma resistance may reach 0.2 Ω during the phase with anomalous resistances and the minimum anode voltage to generate hard X-rays in this phase is about 13 kV [12]. Single and multiple peaks of an electron beam that are highly correlated with the radiated X-rays and anode voltage have been studied [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation